Effects of Entrepreneurial Competence and Planning Guidance on the Relation Between University Students’ Attitude and Entrepreneurial Intention - Ferreira, Aleciane da Silva Moreira (2022)
The objective of this article is to analyse the effect of entrepreneurial competence and planning guidance on the relations between university students’ entrepreneurial attitude and entrepreneurial intention. In this correlational study, the empirical model was tested through Structural Equation Modeling on a sample of 2,771 university students via an online survey at a federal higher education institution in northeastern Brazil. The results point to the moderation effect only of entrepreneurial competence on the relation between entrepreneurial attitude and intention, with this relationship being stronger in students who perceive themselves as more competent. We conclude that self-perception of entrepreneurial skills strengthens the effects of positive attitudes on entrepreneurial career intention, which adds to other evidence of the importance of context and entrepreneurial education for engaging in that career.